Regulation of Anti-Apoptotic SOD2 and BIRC3 in Periodontal Cells and Tissues - Birgit Rath-Deschner; Andressa Vilas Boas Nogueira; Svenja Beisel-Memmert; Marjan Nokhbehsaim; Joni Augusto Cirelli; Sigrun Eick; Nicolai Miosge; Christian Kirschneck; Marco Kesting; James Deschner; Andreas Jäger; Anna Damanaki (2021)
The aim of the study was to clarify whether orthodontic forces and periodontitis interact with respect to the anti-apoptotic molecules superoxide dismutase 2 (SOD2) and baculoviral IAP repeat-containing protein 3 (BIRC3). SOD2, BIRC3, and the apoptotic markers caspases 3 (CASP3) and 9 (CASP9) were analyzed in gingiva from periodontally healthy and periodontitis subjects by real-time PCR and immunohistochemistry. SOD2 and BIRC3 were also studied in gingiva from rats with experimental periodontitis and/or orthodontic tooth movement. Additionally, SOD2 and BIRC3 levels were examined in human periodontal fibroblasts incubated with Fusobacterium nucleatum and/or subjected to mechanical forces. Gingiva from periodontitis patients showed significantly higher SOD2, BIRC3, CASP3, and CASP9 levels than periodontally healthy gingiva. SOD2 and BIRC3 expressions were also significantly increased in the gingiva from rats with experimental periodontitis, but the upregulation of both molecules was significantly diminished in the concomitant presence of orthodontic tooth movement. In vitro, SOD2 and BIRC3 levels were significantly increased by F. nucleatum, but this stimulatory effect was also significantly inhibited by mechanical forces. Our study suggests that SOD2 and BIRC3 are produced in periodontal infection as a protective mechanism against exaggerated apoptosis. In the concomitant presence of orthodontic forces, this protective anti-apoptotic mechanism may get lost.